2015
DOI: 10.1152/japplphysiol.00117.2015
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide during acute hypoxia improves tissue oxygenation in the human brain

Abstract: Low doses of the carbonic anhydrase inhibitor acetazolamide provides accelerated acclimatization to high-altitude hypoxia and prevention of cerebral and other symptoms of acute mountain sickness. We previously observed increases in cerebral O2 metabolism (CMRO2 ) during hypoxia. In this study, we investigate whether low-dose oral acetazolamide (250 mg) reduces this elevated CMRO2 and in turn might improve cerebral tissue oxygenation (PtiO2 ) during acute hypoxia. Six normal human subjects were exposed to 6 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…2,42,48 Another recent report showed that acetazolamide, a carbonic anhydrase inhibitor, abolished the CMRO 2 effect by hypoxia. 56 Since carbonic anhydrase inhibitor has a similar effect as hypercapnia in terms of lowering blood pH, this finding appears to be consistent with the observations of the present study.…”
Section: 34supporting
confidence: 92%
“…2,42,48 Another recent report showed that acetazolamide, a carbonic anhydrase inhibitor, abolished the CMRO 2 effect by hypoxia. 56 Since carbonic anhydrase inhibitor has a similar effect as hypercapnia in terms of lowering blood pH, this finding appears to be consistent with the observations of the present study.…”
Section: 34supporting
confidence: 92%
“…This finding is corroborated by the finding that an increase in CMRO 2 following 6 h of normobaric hypoxia is removed with acetazolamide (Wang et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to altering the neurovascular coupling response, the cerebral metabolic rate of oxygen (CMR O 2 ) does not change during isocapnic hypoxia , with MRI-based evidence indicating that increased neural excitability (and subsequent CMR O 2 ) during PH is a consequence of hypoxic ventilatory response-induced hypocapnia (Smith et al, 2012;Vestergaard et al, 2015). This increase in CMR O 2 has been shown to be mitigated during hypoxia with the administration of acetazolamide (Wang, Smith, Buxton, Swenson, & Dubowitz, 2015), which indicates an important role of hypocapnia and alkalosis in cerebral metabolism during acute hypoxia.…”
Section: Cerebral Haemodynamics and Cognitive Functionmentioning
confidence: 99%